On a singular elliptic problem with variable exponent - FARACI, Francesca (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In the present note we study a semilinear elliptic Dirichlet problem involving a singular term with variable exponent of the following type. Existence and uniqueness results are proved when f ≥ 0. Mathematics Subject Classification (2010): 35J20, 35J65. Received 26 September 2022; Revised 23 January 2023. Published Online: 2023-03-20. Published Print: 2023-04-30